Marburg virus disease in Rwanda: an observational study of the first 10 days of outbreak response, clinical interventions, and outcomes - Gashaija Absolomon; Canita R. Brent; Emmanuel C. Nyabyenda; Kelly Mwiza; Piero Irakiza; Zuki Chiwandire; Caroline Mudereri; Nathalie Umutoni; Sabine Musange; Eric Seruyange; Felix K. Rubuga; Theogene Twagiramugabe; et al. (BMC Medicine)
Abstract Background Marburg virus disease (MVD) is a highly fatal hemorrhagic fever with fatality rates between 33 and 88% in sub-Saharan Africa. Rwanda reported its first MVD outbreak on September 27, 2024. This study assessed Rwanda’s response to its first MVD outbreak, focusing on identifying critical success factors and areas for improvement during the initial 10 days after outbreak declaration. Methods This observational study analyzed publicly available data from daily screenings and outbreak reports provided by the Rwanda Ministry of Health and Rwanda Biomedical Center between September 27 and October 7, 2024. The study examined confirmed cases, deaths, testing rates, and recoveries, including healthcare response measures. Data was collected from checkpoints and passenger screening at entry points, with information aggregated into Rwanda’s Health System. Results By October 7, 2024, Rwanda reported 56 confirmed MVD cases, including 12 deaths and 8 recoveries. Daily screening began on October 3rd, and by October 7th, 2387 individuals were tested, with a positivity rate of 2.3%. Healthcare workers accounted for over 70% of confirmed cases. No new deaths were reported from October 4 (day 7) until October 7th (day 10), though the first 2–3 days after outbreak declaration were critical, with 6 deaths occurring during this period. Rwanda’s response included increased testing, early detection, intensive care management, experimental therapeutics (monoclonal antibodies and remdesivir), and comprehensive contact tracing. Conclusions Analysis of the first 10 days of Rwanda’s MVD outbreak provides valuable insights into effective outbreak response, highlighting the importance of early interventions, healthcare worker protection, enhanced testing, and international collaboration. Early detection and intensive management of cases, including advanced critical care and strong laboratory infrastructure, are essential to reduce early mortality. These findings emphasize the need to strengthen healthcare systems by establishing rapid preparedness and response mechanisms before outbreaks occur and fostering international partnerships to enhance outbreak management and control.